Effect of benzotriazole on the existing pits of copper tube in fire sprinkler system - Eun-Ha Park; Sang-Jin Ko; Jung-Gu Kim (Heliyon, 2023)
In this paper, two leaking tubes were investigated among copper tubes injected with 200 and 400 ppm benzotriazole after 8 years of usage. The electrochemical tests were conducted in simulated pit-out and pit-in environments (i.e., regions outside and inside of the pit) to determine the effect of benzotriazole on the propagation of an existing pit. The electrochemical analysis results showed that 200 and 400 ppm benzotriazole exhibit relatively lower inhibition efficiency in an acidic simulated pit-in environment because of the difficulty of forming a protective film and the benzotriazole cationization.